A de Winter electrocardiographic pattern caused by left main coronary artery occlusion: A case report. Issue 5 (May 2020) - Zhan, Zhong-Qun; Li, Yang; Wu, Li-Hao; Han, Li-Hong
A de Winter electrocardiographic (ECG) pattern comprising precordial junctional ST depression followed by tall, positive symmetrical T waves in leads V1/V2 to V4/V6 is often concomitant with ST elevation in lead aVR. This finding strongly suggests proximal left anterior descending coronary artery occlusion. We described a patient who had the de Winter ECG pattern in leads V2 to V4 by acute left main coronary artery (LMCA) occlusion. The ECG also showed maximal ST depression in leads V4 to V5 and inverted T waves in leads V5 to V6. This finding indicated a global subendocardial ischemia ECG pattern, which suggested LMCA or three-vessel disease. Early recognition of this ECG manifestation is important for averting a disastrous prognosis in acute LMCA occlusion because emergent coronary intervention may be life-saving.